2020
DOI: 10.1177/8755293020906841
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance of squat thin reinforced concrete walls for low-rise constructions

Abstract: Thin reinforced concrete (RC) walls with single layer reinforcement have been used for houses and buildings in several Latin American countries. Although some design codes include recommendations for squat thin walls in low-rise constructions, its seismic performance has not been validated adequately in past earthquakes. This article presents the results of an experimental campaign of nine full-scale specimens conducted to characterize the influence of the steel type, the reinforcement ratio, and the wall thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To examine the accuracy of the proposed strut-and-tie model, experimental wall strengths of 100 specimens collected from past experiments on RC low-rise walls failing in shear 12,19,22,[25][26][27][28][29][30][31][32][33][34][35][36][37] were compared with calculated shear strengths from the model. Subsequently, the predictions from the proposed strut-and-tie model were also compared with predictions from building codes 4,5 and other strut-and-tie models.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the accuracy of the proposed strut-and-tie model, experimental wall strengths of 100 specimens collected from past experiments on RC low-rise walls failing in shear 12,19,22,[25][26][27][28][29][30][31][32][33][34][35][36][37] were compared with calculated shear strengths from the model. Subsequently, the predictions from the proposed strut-and-tie model were also compared with predictions from building codes 4,5 and other strut-and-tie models.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
“…The proposed strut-and-tie model was verified with a total of 100 RC low-rise walls (wall height-length ratio [H w /L w ] less than 2.5) failing in shear that were selected from available literature. 12,19,22,[25][26][27][28][29][30][31][32][33][34][35][36][37] The analysis results show that the model is conservative in predicting the shear strength of RC low-rise walls with an average value of the ratio of the experimental shear strengths to calculated shear strengths V exp /V n of 1.35. While Hwang and Lee's model 15 has the average value V exp /V n of 1.29, which is the closest to 1.00, it overestimates the shear strength of 22 specimens whereas the proposed model only overestimates seven specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, reconnaissance surveys after the Chile (2010) and New Zealand (2010/2011) earthquakes revealed that some RC shear walls in buildings have underperformed and implied the need for review of the design methodology, particularly the ductility levels considered in the design had to be reconsidered in the seismic design (Almeida et al 2017;Blandon et al 2018;Hube et al 2020). Those failed RC walls depicted local buckling of vertical reinforcement and sometimes combined with global instability failures.…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto al comportamiento de muros delgados de CR, Blandon (2018) probó cuatro paredes para caracterizar el comportamiento de edificios de altura media a alta. Este artículo corresponde al trabajo de investigación realizada en la Pontificia Universidad Católica de Chile (Almeida, 2015), se muestra información adicional al trabajo realizado anteriormente por Hube et al, (2020) y describe las actividades experimentales de seis especímenes de muros delgados de hormigón armado a escala real con refuerzo interno de una sola capa. Los muros se detallan con diferentes tipos de acero, proporciones de refuerzo y espesores de muro.…”
Section: Introductionunclassified